EVALUASI KEPUASAN PENUMPANG PADA PELAYANAN DI PELABUHAN PENYEBERANGAN AMOLENGO - Hado; Galih Adi Sulistyo; Ahiula; Maudhy Satyadharma; Sulfiana Fitra Nang; Asriyati (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to evaluate the level of passenger satisfaction with services at the Amolengo Ferry Port. This research was conducted at the Amolengo Ferry Port from July to August 2024, with a sample size of 406 service users at the Amolengo Ferry Port. The results showed that the public satisfaction score was 61, or poor. This issue requires attention from the Amolengo-Labuan Ferry Port Technical Implementation Unit (UPTD), which manages transportation at the Amolengo and Labuan ports, to improve service quality and impact user satisfaction at the Ferry Port.